Hubungan Proses Penyiapan Makanan Pendamping ASI Dengan Kejadian Diare Pada Bayi Usia 7-24 Bulan - Laurentina Dos Reis Lopes; Sih Ageng Lumadi; Feriana Ira Handyana (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2021)
Diarrhea is a symptom with signs of changes in shape and consistency of liquid stools and frequency of defecation more than usual (3 times a day) throwing water five times a day and soft stools. Babies are said to be diarrhea if they have defecated more than three times a day, the effects of the disease are not only for the health of the baby, but also for the process of baby growth and development. This study aims to determine the relationship between the process of preparing complementary foods with the incidence of diarrhea in infants aged 7-24 months in Pandanlandung Village, Wagir District, Malang Regency. The research method uses correlative descriptive with a case control approach. The sample in this study were 130 respondents, with simple random sampling technique. From the Spearman statistical test between the incidence of diarrhea with the preparation process of complementary foods ASI obtained p value = 0,000 (<a = 0,05) with the value of r +.456 so it can be concluded that there is a relationship between the incidence of diarrhea with the process of preparing complementary foods with the incidence of diarrhea in infants aged 7-24 months in Pandanlandung Village, Wagir District, Malang Regency. Means that the worse the process of preparing complementary foods, the higher the incidence of diarrhea. Suggestions from this study are expected respondents can find out the risk factors that can cause diarrhea, as well as the preparation process of MP ASI that is good for babies.